Knowledge and perception in implementing principle 1-4 of MSPO among independent smallholder case of Sungai Rambai, Melaka / Che Nurul Azwin Che Mohd Nordin - Che Mohd Nordin, Che Nurul Azwin (Faculty of Plantation and Agrotechnology, 2019)
The oil palm plantations in Malaysia are largely based on the estate management system and smallholder scheme. The area planted was increasing rapidly from 1.8 million hectares in 1985 becoming a 5.81 million hectare in 2017. However, independent smallholders has possessed a major threat towards Malaysia such as lacking in term of documentation preparation, awareness and higher in cost implementation. Thus, it is perceive that this sector is unproductive and inefficient as compared to the large-scale production system of the estate sector as they are tend to not achieved the standard principle in existing sustainability standard. This research was conducted to study about knowledge and perception of Principle 1-4 Malaysian Sustainable Oil Palm (MSPO) among independent smallholder in Malaysia. This study was conducted in Sungai Rambai, Melaka. The population size of this study is about 50 smallholders. For this study, 44 respondent had been samples. The questionnaires was distributed to the selected smallholders. Pearson correlation is use to analysed the relationship between independent and dependent variables which independent refer to knowledge and perceptions while the dependent variables is referring to principle 1-4 of MSPO. Finding from this study shows that the highest value of 43.6% from Transparency are explained by Perception and the lowest value of 19.4% from Management Commitment & Responsibility are also explained by Perception.